2008
DOI: 10.1590/s0103-64402008000400003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of endodontic pastes with propolis extracts and calcium hydroxide: a preliminary study

Abstract: The purpose of this study was to evaluate the antimicrobial activity of two experimental pastes containing propolis extract associated with calcium hydroxide against polymicrobial cultures collected from 16 necrotic and fistulae root canals in primary molars of 4-8-yearold children of both sexes. The agar-well diffusion technique was used to determine the antimicrobial activity of the following pastes: 11.0% ethanolic extract of propolis (EEP) + calcium hydroxide; and 11.0% extract of propolis without ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 14 publications
2
45
0
3
Order By: Relevance
“…This characteristic combined with its antimicrobial action (14) and capacity to diffuse through the dentinal tubules (15), support its indication as an intracanal medication. Further confirmatory in vivo studies as well as studies on necrotic teeth and/or with periapical lesions should be conducted to substantiate the clinical use of this paste.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This characteristic combined with its antimicrobial action (14) and capacity to diffuse through the dentinal tubules (15), support its indication as an intracanal medication. Further confirmatory in vivo studies as well as studies on necrotic teeth and/or with periapical lesions should be conducted to substantiate the clinical use of this paste.…”
Section: Discussionmentioning
confidence: 89%
“…de Rezende et al (14) evaluated the antimicrobial capacity of a CH and propolis pastes: paste 1 (propolis ethanol extract + CH) and paste 2 (non-alcoholic propolis extract + CH). The authors observed that the pastes were effective, with larger zones of microbial growth inhibition around paste 2.…”
Section: Introductionmentioning
confidence: 99%
“…Their resistance to Ca(OH) 2 reportedly stemmed from their abilities to survive in a high-pH environment 5,18) and to invade dentinal tubules and adhere to collagen in the presence of human serum 19) . Propolis, a centuries-old natural antibiotic, has also been used as an intracanal medicament because of its good antimicrobial activity against a wide range of bacterial species [20][21][22][23] . Therefore, propolis could be used as an alternative intracanal medicament in cases of persistent endodontic infections.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Owing to the antimicrobial and anti-inflammatory properties of propolis, its association with calcium hydroxide has been suggested for use as a root canal dressing. De Rezende et al 16 evaluated two propolis pastes (with and without alcohol) associated to calcium hydroxide. Even though both pastes were found to display antimicrobial action, the nonalcoholic paste produced greater inhibition halos than the paste with alcohol.…”
Section: -13mentioning
confidence: 99%